ACCOUNTING FOR MUZARA’AH CONTRACTS IN AGRICULTURE - Latifah, Eny; Ahmad, Farhan; Sukmana, Wawan (Jurnal Hexagro, 2026)
In farming communities where land and labor are frequently pooled through Islamic partnership agreements, muzara'ah contracts significantly contribute to fair production and income sharing. This study explains the concept of muzara'ah accounting in agriculture, including the recognition and measurement of revenue and costs in muzara'ah contracts and the presentation and disclosure of financial information. The research method is qualitative and uses literature. The results are as follows: First, revenue from muzara'ah contracts is recognized when the harvest is received and can be measured. The recognized revenue is the harvest portion due to the landowner and the farmer under a profit-sharing agreement. Secondly, revenue assessment is based on the fair value of the harvest, which can be determined using current market rates or a mutually agreed value. Third, cost recognition, such as production and other costs, is recognized as an expense in the same period the revenue is recognized. Finally, cost measurement: Costs are measured based on the value incurred to acquire goods or services under the muzara'ah contract, which has important implications for the development of sustainable agricultural systems. First, education on Islamic economic law is needed to strengthen muzara'ah actors' understanding of the contract, ensuring it is executed fairly and transparently. Second, the results of this study can serve as a basis for Islamic financial institutions to design financing models based on the muzara'ah contract. Policymakers, Islamic financial institutions, and agricultural stakeholders should develop definitive accounting guidelines and capacity-building initiatives to ensure the transparent, equitable, and sustainable implementation of muzara'ah contracts. Keywords: Muzara'ah accounting, revenue recognition, cost measurement, Islamic finance, sustainable agriculture